A Field Guide to Non‐Onsager Quantum Oscillations in Metals - Valentin Leeb; Nico Huber; Christian Pfleiderer; Johannes Knolle; Marc A. Wilde (Advanced Physics Research)
Abstract Quantum oscillation (QO) measurements constitute a powerful method to measure the Fermi surface (FS) properties of metals. The observation of QOs is usually taken as strong evidence for the existence of extremal cross‐sectional areas of the FS according to the famous Onsager relation. Here, mechanisms that generate QO frequencies that defy the Onsager relation are reviewed and material candidates are discussed. These include magnetic breakdown, magnetic interaction, chemical potential oscillations, and Stark quantum interference, most of which lead to signals occurring at combinations of “parent” Onsager frequencies. A special emphasis is put on the recently discovered mechanism of quasi‐particle lifetime oscillations (QPLOs). This work aims to provide a field guide that allows, on the one hand, to distinguish such non‐Onsager QOs from conventional QOs arising from extremal cross sections and, on the other hand, to distinguish the various non‐Onsager mechanisms from each other. A practical classification of non‐Onsager QOs is given in terms of the prerequisites for their occurrence and their characteristics. It is shown that, in particular, the recently discovered QPLOs may pose significant challenges for the interpretation of QO spectra, as they may occur quite generically as frequency differences in multi‐orbit systems, without the necessity of visible “parent” frequencies in the spectrum, owing to a strongly suppressed temperature dephasing of QPLOs. An extensive list of material candidates is presented where QPLOs may represent an alternative explanation for the observation of unexpected QO frequencies.